The Effectiveness of the Indonesian Government's Economic Stimulus Policy during the Covid-19 Pandemic - Danni Pangaribowo; Feni Rosalia; Maulana Mukhlis; M Fajar Novriansyah; Ni Kadek Poniasih (Jurnal Public Policy, 2022)
The COVID-19 pandemic has had a devastating impact on the economy. The social restriction policies implemented have an impact on economic activity. The limited activity in the economic sector has an impact on national contraction. At its peak in the second quarter of 2020, the economy experienced a decline of minus 5.35 percent. To deal with these rights, the Government then implements a policy pattern to stimulate the economy. Starting from the ratification of Law No. 1 of 2020 as the foundation of the government's tactical policies. Furthermore, the OJK will apply tax incentives and credit programs. The government then implemented the Covid-19 Handling and National Economic Recovery (PEN) program. This program allocates budget to several specific sectors. The sectors in question include health, MSME stimulus, social protection, tax and business incentives, as well as priority sectors. In terms of effectiveness, this program absorbs the budget quite well and shows positive results on economic growth.